Tetramerization of human guanylate-binding protein 1 is mediated by coiled-coil formation of the C-terminal α-helices - Syguda, Adrian; Bauer, Michael; Benscheid, Utz; Ostler, Nicole; Naschberger, Elisabeth; Ince, Semra; Stürzl, Michael; Herrmann, Christian (Febs Journal, 2012)
The human guanylate-binding protein 1 (hGBP1) is a large GTP-binding protein belonging to the dynamin family, a common feature of which is nucleotide-dependent assembly to homotypic oligomers. Assembly leads to stimulation of GTPase activity, which, in the case of dynamin, is responsible for scission of vesicles from membranes. By yeast two-hybrid and biochemical experiments we addressed intermolecular interactions between all subdomains of hGBP1 and identified the C-terminal subdomain, α12/13, as a new interaction site for self-assembly. α12/13 represents a stable subdomain of hGBP1, as shown by CD spectroscopy. In addition to contacts between GTPase domains leading to dimer formation, the interaction between two α12/13 subdomains, in the course of GTP hydrolysis, results in tetramer formation of the protein. With the help of CD spectroscopy we showed coiled-coil formation of two α12/13 subdomains and concentration-dependent measurements allow estimating a value for the dissociation constant of 7.3 μm. We suggest GTP hydrolysis-driven release of the α12/13 subdomain, making it available for coiled-coil formation. Furthermore, we can demonstrate the biological relevance of hGBP1 tetramer formation in living cells by chemical cross-link experiments. © 2012 FEBS.
Created from Fastlane, Scopus look-up
Keywords: aluminum fluoride; dynamin; protein dimer; protein-protein association; self-assembly